Analisis Total Productive Maintenance (TPM) dengan Menggunakan Metode Overall Equipment Effectiveness (OEE) pada Mesin Blowing - Ardiansyah, Mochammad Rizal; Nuriyanto, Nuriyanto (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to evaluate the effectiveness of the palletizer machine at PT XYZ using the Overall Equipment Effectiveness (OEE) method and to identify the main causes of failure through the Failure Mode and Effect Analysis (FMEA) approach. OEE measurement includes three key parameters: availability, performance rate, and quality rate. The results show that the OEE value ranges between 91%–93%, which exceeds the JIPM standard of 85%, but has yet to consistently meet the company's production target of 91%. The Six Big Losses analysis revealed that the highest loss was due to equipment failure, accounting for 1.7%, with the palletizer contributing 55% of the total technical downtime. FMEA identified three critical components with the highest Risk Priority Numbers (RPN): the push box motor, sliding motor, and hydraulic oil pump. Root causes were further explored using a fishbone diagram